Tim Rogan. The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. - Dale, Gareth (The American Historical Review, 2019)
When the capitalist system hits the rocks and neoclassical economics loses its aura, alternative traditions invite attention. Tim Rogan’s The Moral Economists i
Keywords: The Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson, and the Critique of Capitalism (book); book review; capitalism

The political economy of family policy expansion: Fostering neoliberal capitalism or promoting gender equality supporting social reproduction? - Ferragina, Emanuele (Review of International Political Economy, 2019)
This article presents a new theoretical and empirical approach to understand family policy expansion in relation to the political economy of welfare state retrenchment and social reproduction in 23 OECD countries. From a Polanyian perspective, this expansion can be interpreted as a movement toward commodification and liberalization, and a countermovement of gender liberation. The first movement seems to characterize family policy expansion as a tool to foster neoliberal capitalism and the advent of a Schumpeterian Workfare State, conspiring with welfare state retrenchment to encourage employment within an environment of growing precarization. The second movement appears to assuage the social reproduction crisis. This countermovement seems to act as a cushion to soften the shift from a male income earner toward a dual earner model, supporting working parents in meeting escalating childare costs. Looking at the expansion of childcare spending and the retrenchment of minimum income guarantees for couples with children, an empirical illustration of this concomitant 'double movement' reveals that the first holds sway over the second in most countries. Furthermore, household income and maternal levels of education impact on childcare usage, magnifying the negative distributional consequences of cutting minimum income guarantees in favor of childcare.
Keywords: Schumpeterian workfare state; childcare; commodification; countermovement; family policy; gender equality; neoliberalism; social reproduction; welfare state retrenchment

On Misunderstanding the Second Contradiction Thesis - Rudy, Alan P. (Capitalism, Nature, Socialism, 2019)
James O'Connor's "second contradiction" thesis is widely misunderstood as an ecological crisis theory. Most of the criticisms of the theory derive from this misreading, including those which ignore relations between ecological, personal and communal conditions and those which see the "first" and "second" contradictions as materially distinct. O'Connor himself is partially responsible for the misreading, however. His writings tended to put the ecological out front, and his use of Polanyi's romantic idea of "fictitious commodities" reinforced that tendency. The defense developed here rejects ecologistic readings, ties the second contradiction thesis backwards and forwards in O'Connor's work, unpacks the meaning of "conditions" for Marx and O'Connor, and suggests that Neil Smith's argument that capitalist second natural relations generate qualitatively new processes by which nature, human nature and space are produced would have served O'Connor better.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; POLANYI, Karl, 1886-1964; SMITH, Neil; conditions of production; contradiction; ecological Marxism; ecologism; environmental marxism; human behavior; second contradiction

SEE Beyond Substantive Economics: Avoiding False Dichotomies - Spash, Clive L. (Ecological Economics, 2019)
The proposal has been put forward that ecological economics seek to become substantive economics (Gerber and Scheidel 2018). This raises important issues about the content and direction of ecological economics. The division of economics into either substantive or formal derives from the work of Karl Polanyi. In developing his ideas Polanyi employed a definition from Menger and combined this with Tönnies theory of historical evolution. In this paper I explore why the resulting substantive vs. formal dichotomy is problematic. In particular the article exposes the way in which trying to impose this dichotomy on history of economic thought and epistemology leads to further false dichotomies. Besides Polanyi, the positions of other important thinkers informing social ecological economics (SEE) are discussed including Neurath, Kapp and Georgescu-Roegen. The aim is to clarify the future direction of ecological economics and the role in that future of ideas raised under the topic of substantive economics.
Keywords: economic anthropology; epistemology; formal economics; history of thought; social ecological economics; substantive economics

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Keywords: BLOCK, Fred L.; SOMERS, Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

De-privatisation and remunicipalisation of urban services through the pendulum swing: Evidence from Germany - Weber, Gabriel; Cabras, Ignazio; Frahm, Lars-Gunnar (Journal of Cleaner Production, 2019)
This paper explores and examines the distribution of environmental conflicts in Germany between 1985 and 2015, analysing the main causes for environmental conflicts related to privatisation and de-privatisation processes of urban services in 80 German cities. Using information collected via means of a Delphi Method based on focus groups with experts, we identify 90 cases of large-scale privatisation initiatives involving urban services occurred in different fields within the period considered. In 38 cases, privatisation was reversed due to initiatives undertaken by environmental justice organisations and other local grassroots groups promoting de-privatisation and re-municipalisation. In another 30 cases, privatisation was prevented as a result of these initiatives. Findings from our analysis indicate that de-privatisation initiatives and potential conflicts related to them are frequently driven by grassroots organisations promoting the provision of commons-based urban services. Our findings also suggest that privatising services in the energy, water supply and waste management sectors is likely to negatively affect the quality of service supply and increasing prices for urban residents. Image 1 • This paper explores ecological conflicts in Germany by using comparative analysis, statistics, and political ecology. • It investigates the main causes for conflicts related to privatisation and de-privatisation of urban services. • With a Delphi Method and focus groups with experts, we identify 90 cases of large-scale privatisation. • 38 initiatives of de-privatisation are identified, many driven by grassroots organizations reclaiming the concept of commons. • De-privatisation initiatives indicate a pendulum swing towards more socially controlled production.
Keywords: Delphi method; Germany; Polanyi's pendulum; city dwellers; environmental justice; pendulums; political ecology; privatisation and de-privatisation; remunicipalisation; services and utilities; sustainable cities; urban areas; water supply management

Global Cities as Market Civilisation - Curtis, Simon (Global Society: Journal of Interdisciplinary International Relations, 2019)
Building upon interdisciplinary efforts to understand the origins, logic and significance of global cities, this article argues that global cities should be seen as a critical component and outcome of a political project to generate a global market society. Global cities should be seen as the successful implementation of free-market political philosophy, constructed and defended by a particular historical configuration of international society. The historical transformation of urban form signalled by the "global city" concept is tightly bound to the neoliberal restructuring of the world economy in the 1970s, underpinned by US hegemonic power. The first part of this article argues that the distinctive historical origin of global cities has shaped their current trajectories and draws the horizon of their future prospects. Having established the connection between liberal world order and global cities, the second part of the article argues that the contemporary form of the global city is under threat from two sources. The first threat is internal to the global city form itself. Global cities have internalised the contradictory forces of market liberalism. They have registered astonishing economic growth over the last four decades, and generated vast material and intellectual resources. But, at the same time, they have become deeply divided and polarised in ways that threaten the urban fabric. The second source of threat comes from the possible weakening or collapse of liberal world order, with the accelerating decline of US hegemony. Drawing on aspects of Karl Polanyi's analysis of the nineteenth-century "great transformation", the article argues that a number of future trajectories for the global city can be identified in the contemporary moment.
Keywords: global city; market liberalism

Networked but Commodified: The (Dis)Embeddedness of Digital Labour in the Gig Economy - Wood, Alex J; Graham, Mark; Lehdonvirta, Vili; Hjorth, Isis (Sociology, 2019)
This article investigates the (dis)embeddedness of digital labour within the remote gig economy. We use interview and survey data to highlight how platform workers in Southeast Asia and Sub-Saharan Africa are normatively disembedded from social protections through a process of commodification. Normative disembeddedness leaves workers exposed to the vagaries of the external labour market due to an absence of labour regulations and rights. It also endangers social reproduction by limiting access to healthcare and requiring workers to engage in significant unpaid 'work-for-labour'. However, we show that these workers are also simultaneously embedded within interpersonal networks of trust, which enable the work to be completed despite the low-trust nature of the gig economy. In bringing together the concepts of normative and network embeddedness, we reconnect the two sides of Polanyi's thinking and demonstrate the value of an integrated understanding of Polanyi's approach to embeddedness for understanding contemporary economic transformations.
Keywords: commodification; digital labour; disembeddedness; embeddedness; freelancing; gig economy; outsourcing

Contesting household debt in Croatia: the double movement of financialization and the fetishism of money in Eastern European peripheries - Mikuš, Marek (Dialectical Anthropology, 2019)
Croatia has experienced a marked boom in household debt in the 2000s. Much of this lending took high-risk and predatory forms that transferred significant risks to debtors, which in turn became the target of contestation by debt activists. This paper uses the Polanyian idea of "double movement" to show how the Croatian debt contestations responded to the distinctively peripheral form of financialization in Eastern Europe, characterized by unequal geoeconomic relationships and an intensified expropriation of debtors. This framework further highlights the importance of money in contemporary credit/debt relationships and their contestation, which has so far received insufficient attention in relevant anthropological scholarship. Instead of the currently fashionable credit theories of money, the paper uses the Marxian concept of the fetishism of money to unpack the roles of money in these processes. The analysis of discourses and practices of two groups of debtors and activists reveals how they used nationalist ideological frameworks and institutional channels such as litigation, again largely ignored by existing anthropological literature, to challenge the particular inequalities of peripheral financialization and the expropriation of debtors through the lenders' predatory manipulations of the money fetish.
Keywords: Croatia; Eastern Europe; consumer credit; contestation; debtor & creditor; financialization; household debt; money

Islam, entrepreneurship, and embeddedness - Tok, M. Evren; Kaminski, Joseph Jon (Thunderbird International Business Review, 2019)
This study centers on the premise that entrepreneurship is an embedded process. Although "the entrepreneur" is inherently an "individual," entrepreneurship can never be fully disembedded from the more general social settings within which any business venture is situated. An Islamic‐based economic discursive framework should be cognizant of the different forms of sociality, spatiality, and community as well as the various norms, codes, and symbols that define society more generally. The work of Karl Polanyi on embeddedness is engaged and juxtaposed with Islam's understanding of the ideal mode of economic discursive practices. Islamic economic models and Polanyi are both critical of the corrosive effects of unbridled capitalism and individualism that ultimately lead to reification and exploitation. The conclusion recommends more small‐N case studies by researchers and entrepreneurial educational materials that emphasize the importance of networks and local embeddedness.
Keywords: Islam; POLANYI, Karl, 1886-1964; discursive practices; economic models; entrepreneurship; teacher researchers

Problematizing capitalism(s): Big difference? - Peck, Jamie (Environment & Planning A, 2019)
In the article, the author examines the social science theories of Fred Block, particularly on such topics as capitalism, finance, markets, and government. Other topics include Block's opinions on Polanyian socioeconomics, his thoughts on economic diversity and capitalist transformation, as well as the universalist model of capitalism as free-market globalism.
Keywords: BLOCK, Fred L.; capitalism; finance; free enterprise; markets; social sciences; the state

Soziale Bewegungen und Gewerkschaften im Wechselspiel - Pernicka, Susanne (Forschungsjournal Soziale Bewegungen, 2019)
Vereinzelte Verweise auf westmitteleuropäische Länder, die USA oder Australien machen aber deutlich, dass die neoliberale Politik auch in diesen Ländern zu einer Verschärfung der Spaltungen zwischen verschiedenen Gruppen auf dem Arbeitsmarkt und zwischen diesen und den "Abgehängten" ohne Aussicht auf eine dauerhafte Integration in den Arbeitsmarkt geführt hat. Die Fragen nach der Nachhaltigkeit von Allianzen zwischen Gewerkschaften und sozialen Bewegungen, den politischen und gesellschaftlichen Orientierungen (kosmopolitische Öffnung versus nationalistische und gruppenspezifische Schließungen) sowie deren Effekten bleiben aber letztlich offen und können durch den Verweis auf Polanyis "Pendel" zwischen ökonomischer Liberalisierung und protektionistischer Gegenbewegung kaum zufriedenstellend beantwortet werden. Wie die Herausgeber des Sammelbandes in den Schlussfolgerungen betonen, handelt es sich bei der aktuellen Phase des Neoliberalismus um eine seit mehreren Dekaden andauernde Bewegung von oben, die ungeachtet der Finanz- und Eurokrise(n) ihre hegemoniale Stellung kaum eingebüßt und bestehende Spaltungen und Konflikte zwischen und innerhalb von Gewerkschaften, sozialen Bewegungen und Parteien stark vergrößert hat.
Keywords: Polanyi's pendulum; pendulum; social movements

Economic Liberalism and the State: Dismantling the Myth of Naïve Laissez-Faire - Stahl, Rune Møller (New Political Economy, 2019)
The article offers a critique of the prevailing understanding of the relationship between neoliberalism and classic nineteenth-century liberalism in contemporary international political economy (IPE) and offers a redefinition inspired by Polanyi and Gramsci. Within critical IPE studies, a consensus has emerged that neoliberalism cannot be reduced to a simple attempt to roll back the economy and let loose free-market forces. However, this insight relies on contrasting neoliberalism with a classic liberalism, that is, a simple attempt to implement just this naïve laissez-faire ideology. In contrast, this article argues that nineteenth-century liberalism is also characterised by an active use of state and legislative power. Through a historical study of two cases from nineteenth-century Britain, Poor Law reform and the Gold Standard, the paper will argue that state action played a central role even during the heyday of laissez-faire liberalism. With a starting point in Polanyi's dictum that 'laissez-faire was planned', this reinvestigation will point towards a need to develop a more nuanced understanding of the distinctions between economic theory, ideology, and practical policy, as well as pointing towards a general reinterpretation of the role of the state in liberal economic ideology.
Keywords: classical liberalism; critical political economy; economic governance; history of economic thought; international political economy; liberalism; liberty; neoconservatism; neoliberalism; ordoliberalism; state theory

Knowledge and social freedom - Rief, Silvia (Journal of Cultural Economy, 2019)
Keywords: Karl Polanyi's Vision of a Socialist Transformation (Book); book review; commentary; freedom

Ethnoracial Populism: An Alternative to Neoliberal Globalization? - Antonio, Robert J. (Social Epistemology, 2019)
Worldwide emergence of strongmen leaderships and eroded or failed democracies suggest that the era of unchallenged neoliberal hegemony may be winding down and that alternatives are rising. The presidential election of Donald Trump has inspired rightwing populists at home and abroad. This paper will analyze the Trumpist fusion of authoritarian ethnoracial nationalism with neoliberal adventure capitalism and the broader matter of how neoliberal de-democratization opens way for right-wing populism and illiberal capitalism. The topics will be explored in part through discussions of earlier theories of Friedrich Hayek, Carl Schmitt, John Dewey, and Karl Polanyi that have been revived and deployed in the current debates over neoliberalism, populism, and democracy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; Presidential elections; SCHMITT, Carl, 1888-1985; Trumpism; de-democratization; ethnoracial populism; globalization; nationalism; neoliberalism; populism; right-wing populism

Karl Polanyi and the Law of Market Society - Frerichs, Sabine (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi started his career as a doctor of law and practiced law for a while; but he did not become a legal scholar. As an economic historian, anthropologist, or sociologist, he was concerned with the relation of economy and society. But even though law is an important factor in mediating this relationship, Polanyi gave little attention to the law as such. As part of an endeavour to advance a ‘Polanyian’ economic sociology of law, this article develops the ‘law of market society’ as an analytical category. For this purpose, three argumentative strategies are combined. First, the article draws on The Great Transformation to reconstruct the role of law in the processes of commodification and decommodification. Second, it turns to Marxist scholarship to explore the conceptual link between law and economics and to ponder to what extent law itself can become a commodity. Third, it links Polanyi’s approach with American institutionalism, and Commons’ work in particular, to show how the evolution of the ‘law of market society’ can also be understood as a collective enterprise which continuously evolves. It is argued that these perspectives complement each other and help to bring the law back in where it is missing.
Keywords: law of market society; sociology of law

Historicizing Karl Polanyi - Gräser, Marcus (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi’s book The Great Transformation has found great resonance in the social sciences in recent years—especially in sociology, political economy and political science. The interest in Polanyi among historians is still modest in comparison. There are not enough studies that treat Polanyi as an object of intellectual history/history of science, nor has Polanyi been used hitherto as an idea-giver for the growing field of global history—despite the fact that his book can be understood as global history. It is high time to “historicize” Polanyi in several ways.
Keywords: history of science; intellectual history

Commodity Studies with Polanyi: Disembedding and Re-Embedding Labour and Land in Contemporary Capitalism - Langthaler, Ernst; Schüßler, Elke (Österreichische Zeitschrift für Soziologie, 2019)
This article aims to inform current debates in the field of transnational commodity studies through a Polanyian lens. Polanyi reminds us of the need to pay attention to the “double movements” in which fictitious commodities are disembedded from and re-embedded in society. We focus on two fictitious commodities, labour and land, which are conventionally treated as mere inputs for the production of genuine commodities. Through investigating the disembedding and re-embedding of labour in the garment industry, and of land in the agro-food sector since the 1970s, we gain insights regarding the commodification of fictitious commodities in the context of transnational commodity chains. The developments in both fields imply not just simple double movements, but complex entanglements of disembedding and re-embedding dynamics at the interface of state, business and civil society actors.
Keywords: commodity studies; double movement

The Rise of Populist Movements in Europe: A Response to European Ordoliberalism? - Cayla, David (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
This article aims to explain the contemporary emergence of populism in the European Union. According to Polanyi's double movement framework, the emergence of these political forces can be understood as the result of protective responses from societies weakened by difficult market adjustments. Since the Single Act treaty (1986), the European economy took a path that intended to create a supranational self-adjusting markets economy based on the ordoliberal philosophy. However, by detaching the economic sphere from the reach of politics, the European Single Market has injured some important social institutions. The rise and the diversity of populisms in the European Union can therefore be explained by an attempt to preserve some national institutions that were diversely impacted by the market forces.
Keywords: European Single Market; free enterprise; institutional economics; international relations; neoliberalism; ordoliberalism; populism; social functions; social institutions

Doing justice to Karl Polanyi - Devine, Pat (Capitalism, Nature, Socialism, 2019)
Keywords: POLANYI, Karl, 1886-1964; book review; economic activity; economics; social control; social forces

State Capitalism Revisited: A Review of Emergent Forms and Developments - Dolfsma, Wilfred; Grosman, Anna (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Even when the neoliberal ideology of the free market was more dominant than it now is, the state was involved in economic activities that could be undertaken by private firms. State capitalism takes increasingly diverse forms, including beyond direct, partial or even indirect ownership. This paper briefly reviews some of these forms without claiming to be exhaustive as the shape state capitalism takes differs widely across the institutionalized contexts of countries. We assess state capitalism using Polanyi's double movement framework and argue that this framework needs adaptation to novel forms of state capitalism that include, e.g., state-owned multinationals and sovereign wealth funds.
Keywords: SOMNCs; capitalism; double movement; economic development; economic systems; international relations; investments; profit; sovereign wealth funds; state capitalism; state-owned enterprises

Remittances and Households in the Age of Neoliberal Uncertainty - Khanal, Kalpana; Todorova, Zdravka (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
International migration and remittance flows have been reframed as catalysts for poverty reduction and development through marketization. Growth, measurement, and promotion of global remittances have emerged against the backdrop of neoliberal structural adjustment programs and financialization. Those processes have paralleled the emergence of the transnational household as a global institution. The article suggests that transnational households characterize a new stage of neoliberal capitalist development. The article revisits Karl Polanyi's The Great Transformation and discusses how active governance and neoliberal discourse regulate and frame labor and remittances as "fictitious commodities." Further, it is argued that transnational households take active roles in Polanyi's "double movement," by providing social protection amidst narrow public responsibility for provisioning. The article identifies this as a new element of "the great transformation," and referring to J. K. Galbraith, as a new age of neoliberal uncertainty.
Keywords: double movement; economic development; fictitious commodities; income; neoconservatism; neoliberalism; remittances; transnational households

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

Populism in Times of Attempted Unity of Heterogeneous Social Demands - Wagner, Paulus (International Spectator, 2019)
Keywords: HOLMES, Christopher; POLANYI, Karl, 1886-1964; Polanyi in Times of Populism: Vision & Contradiction in the History of Economic Ideas (Book); book review; economic policy; nonfiction; populism

The Last Gasp of Neoliberalism - Watkins, John P.; Seidelman, James E. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
The ideas of both Thorstein Veblen and Karl Polanyi shed light on understanding the last gasp of neoliberalism. The last gasp refers to Donald Trump's abandonment of free trade, long considered a cornerstone of the neoliberal agenda, and his overt attacks on democratic institutions. In Trump, neoliberalism's attempt to overcome the gridlock of liberal democracy has revealed its fascist leanings. Both Polanyi and Veblen warned about the trend towards fascism. Trump was elected, in part, by filling the void left by the factioning of neoliberalism, in part by the injustice felt by people in rural areas, those with stagnant incomes, white males, and others. Trump has transcended the neoliberal agenda, approaching market relations from the point-of-view of the fight. The emergence of a predatory culture, in both the domestic and international realms, resembles the culture outlined in Veblen's The Theory of Business Enterprise. Trump's actions reveal the need to extend Polanyi's idea of social protection given the negative effects of modern technology and Trump's efforts to dismantle or reduce some regulatory agencies. Changing demographics and the adverse reaction to Trump's fascist leanings may yet see the emergence of a new progressive era, suggesting, at least, that Trump represents the last gasp of neoliberalism.
Keywords: POLANYI, Karl, 1886-1964; VEBLEN, Thorstein, 1857-1929; capitalism; democracy; double movement; fascism; international relations; neoliberalism

Financialization, Class Interests, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Many observers expected a stronger countermovement against neoliberalism following the Great Recession. This article argues that such a protective response failed to materialize because the financialization process has aligned the preferences of labor and rentier classes. The result has been weaker support in democracies for expansionary monetary and fiscal policies during the early stages of recessions, which further lowers aggregate spending by increasing uncertainty. Thus, reversing the culture of financialization may be a necessary condition for preventing and responding to financial crises.
Keywords: Polanyi, Karl, 1886-1964; business development; double movement; economic development; economic policy; financial crises; financialization; macroeconomic policy; monetary policy

Absolute Capitalism - Foster, John Bellamy (Monthly Review: An Independent Socialist Magazine, 2019)
The article deals with the emergence of absolute capitalism due to the efforts of states to promote social reproduction. It explores the association between absolute capitalism and neoliberalism, a ruling-class political-ideological project that is connected to the rise of monopoly-finance capital. Some 20th century thinkers had their own ideas about absolute capitalism, including Karl Polanyi and John Maynard Keynes.
Keywords: KEYNES, John Maynard, 1883-1946; POLANYI, Karl, 1886-1964; capitalism; finance capitalism; neoliberalism; social reproduction

La società di mercato e le sue trasformazioni. Attualità di Karl Polanyi - Cangiani, Michele (Itinerari di ricerca storica, 2019)
ItIl neoliberalismo è sorto dall'esigenza di superare la crisi degli anni Settanta del secolo scorso, ma ha portato a una nuova crisi, da molti detta "sistemica". Siamo quindi sollecitati a riflettere sulle caratteristiche fondamentali del nostro sistema sociale e sulla sua storia. A questo fine, l'opera di Karl Polanyi fornisce preziose indicazioni. In essa, da una parte, la società di mercatocapitalistica viene definita in generale, nella sua specificità, mediante una comparazione a vasto raggio con le società precedenti. D'altra parte, viene analizzata la "trasformazione" di tale società da un assetto istituzionale all'altro, attraverso un periodo di crisi e di conflitto sociale. Poiché, tuttavia, le ragioni profonde della crisi permangono nel nuovo assetto insieme con le caratteristiche più generali del sistema sociale, la crisi tende a ripresentarsi, insieme all'esigenza di una nuova trasformazione istituzionale. Questo articolo intende mostrare che tale tesi è perlomeno implicita negli scritti di Polanyi e che quindi non solo la sua teoria della società di mercato in generale, ma anche le sue analisi delle vicende della "grande trasformazione" fra le due guerre mondiali possono essere utili per comprendere gli sviluppi ulteriori della nostra società fino alla situazione attuale.EnNeoliberalism arose from the need to overcome the crisis of the 1970s, but led to a new "systemic" crisis. We are therefore urged to reflect on the fundamental characteristics of our social system and its history. To this end, Karl Polanyi's work provides valuable suggestions. In it, on the one hand, the capitalist market society is defined in general, in its specificity, through a widerange comparison with previous societies. On the other hand, the "transformation" of that society is analyzed, from one institutional setup to another, through periods of crisis and social conflict. Since the deep reasons of the crisis remain in the new set-up, together with the more general characteristics of the social system, the crisis tends to recur, together with the need for a new institutional transformation. The present paper intends to show that this thesis is, at least, implicit in Polanyi's writings; therefore, not only his theory of the market society in general, but also his analysis of the events of the "great transformation" between the two world wars can be useful in understanding further developments of our society up to the current situation.
Keywords: capitalism; capitalismo; crisi; crisis; transformation; trasformazione

The New Alchemy: Economic liberalism, neoliberalism, and Thomas Pynchon's Against the Day - Carswell, Sean (Textual Practice, 2019)
This article utilises Karl Polanyi's landmark 1944 text The Great Transformation to explicate economic liberalism as it is represented in Thomas Pynchon's Against the Day. Polanyi argues that a fundamental flaw of economic liberalism is its treatment of labour and land as commodities. This commodification leads to economic and ecological disasters. Pynchon demonstrates these disasters throughout his encyclopaedic novel. Further, using Pynchon's metaphor of bilocation – literally being in two places at the same time – this article 'bilocates' the economic liberalism represented in the novel with contemporary neoliberalism, specifically as neoliberalism is characterised by David Harvey and Wendy Brown. Ultimately, this exploration leads to a discussion of freedom within a neoliberal society, particularly as it is envisioned in Pynchon's novel.
Keywords: Against the Day (book); BROWN, Wendy; HARVEY, David; PYNCHON, Thomas, 1937-; economic liberalism; economics; fictitious commodities; globalization; neoliberalism

Can Karl Polanyi Explain the Anthropocene? The Commodification of Nature and the Great Acceleration - Steinberg, Ted (Geographical Review, 2019)
The most important historical work on the Anthropocene to date is J. R. McNeill and Peter Engelke’s The Great Acceleration: An Environmental History of the Anthropocene since 1945 (2016). The authors argue that the Anthropocene began in 1945, not in the eighteenth century, as some scientists have proposed. They single out unintentional “human actions” as the driving force behind the significant changes in biogeochemical processes unfolding since the middle of the twentieth century (McNeill and Engelke 2016, 4, 208). The main title of their book mimics a phrase first used at a 2005 conference on the future of the planet and refers to the escalating human threats to the so-called Earth System. The title was meant to parallel Karl Polanyi’s The Great Transformation: The Political and Economic Origins of Our Time (1944). Born in 1886 in Hungary, Polanyi became one of the world’s greatest economic historians. In an endnote to their book, McNeill and Engelke explain that Polanyi saw the “market economy” as a recent invention that “must be understood as embedded in social traditions, customs, and habits of the mind.” Likewise, they continue, human impacts on global ecology “are embedded in societies and their traditions” (McNeill and Engelke 2016, 213).
Keywords: ENGELKE, Peter; Great Acceleration: An Environmental History of the Anthropocene Since 1945, The (Book); MCNEILL, J. R.; anthropocene epoch; capitalism; globalization; nonfiction; urban development

Neoliberal Legality as Dual Process: Embeddedness, Courts and Crime Prevention in the United States - Campeau, Holly; Levi, Ron (British Journal of Criminology, 2019)
This article advances research on 'neoliberal legality' to focus on the role of courts in response to neoliberal crime prevention approaches. Drawing on Karl Polanyi's analysis of embeddedness in market capitalism, along with criminological research on the penal state, we analyse three case studies reflecting central crime prevention approaches of the neoliberal era in the United States. We find that neoliberal legality is more complex than simply legitimating or resisting neoliberal policies. We highlight how courts did both at once—they moderated the harshest edges of neoliberal policies through alternative symbolic frames, yet in so doing also legitimated the core of neoliberal crime prevention efforts. We argue that neoliberal legality operates through this dual process, in which the basic thrust of neoliberalism is legitimated by also having policies moderated, recast and embedded within other social and juridical expectations.
Keywords: POLANYI, Karl, 1886-1964; United States; capitalism; courts; crime prevention; embeddedness (socioeconomic theory); law; neoliberal legality; neoliberalism; penal state

MARX E POLANYI: A CONSTRUÇÃO DE UMA EPISTEMOLOGIA CRÍTICA AO LIBERALISMO ECONÔMICO - Amaral, Ticiana (Revista Café com Sociologia, 2019)
O propósito do artigo é, a partir das obras de Marx e Polanyi, realizar uma revisão teórica centrada no pensamento crítico que os autores direcionaram à Economia Política burguesa, especialmente às ¨falácias epistemológicas¨, cujo objetivo seria de justificar um modo de produção desumanizante, que submete as demais esferas da vida social às leis de mercado, e o de naturalizar leis próprias, através da separação institucional entre sociedade e economia. Busca-se demonstrar como, apesar de diferenças teóricas e metodológicas, Marx e Polanyi elaboraram uma crítica sólida aos postulados do liberalismo econômico, em específico ao que concerne a visão de natureza humana e livre mercado.
Keywords: MARX, Karl, 1818-1883; economic liberalism; epistemology; homo economicus

The future of capitalism: Trends, scenarios and prospects for the future - Delanty, Gerard (Journal of Classical Sociology, 2019)
The article provides a framework for thinking about how the question of the future of capitalism might be addressed. One of the problems resides in the very definition of capitalism and of what its defining features consist of and whether we should be talking about 'capitalist society' or the 'capitalist economy' or some kind of post-capitalist condition. Following Polanyi, Castoriadis and Habermas, it is argued that capitalism and democracy together constitute the defining dynamics of modernity and that the resulting tensions will provide momentum for the main circuits of potential change. Five scenarios for looking at the future are discussed. These will form the main substance of the article: varieties of capitalism, systemic crises of capitalism, catastrophic collapse, low growth capitalism and post-capitalism. In conclusion, it is argued that there are various possibilities that can be understood in terms of transitions, breakdown or transformation, but a likely future trend will be less the end of capitalism than the harnessing of 'super-capitalism' and that there are limits to the accumulation of capital.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; capital; capitalism; democracy; future of capitalism; modernity; neoliberalism; varieties of capitalism

Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies

Postneoliberalism as institutional recalibration: Reading Polanyi through Argentina’s soy boom - Berndt, Christian; Werner, Marion; Fernández, Víctor Ramiro (Environment and Planning A: Economy and Space, 2019)
While postneoliberalism is often interpreted as a societal reaction against the deleterious effects of marketization in Latin America, this paper develops a finer-grained Polanyian institutional analysis to gain better analytical purchase on the ambivalent outcomes of postneoliberal reforms. Drawing on recent insights in economic geography, and in dialogue with the Latin American structuralist tradition, we elaborate our framework through a case study of the Argentinian soy boom of the 2000s, identifying forms of market extension, redistribution, reciprocity and householding that facilitated this process. We argue for a multi-scalar approach that balances attention to national and extra-local dynamics shaping the combination of these forms, identified through the lens of the “fictitious commodities” of the soy boom: money (credit, currency and cross-border capital flows), land (in the agricultural heartland and frontier regions), labor (transformed and excluded in a “farming without farmers” model) and, we add, knowledge (biotech). Our analysis identifies internal tensions as well as overt resistance and “overflow” that ultimately led to the collapse of postneoliberal regulation of the soy complex, ushering in a wider, market-radical counter-movement. Refracting double-movement-type dynamics through the prism of heterodox institutional forms, we argue, allows for a better grasp of processes that underlie institutional recalibrations of progressive and regressive kinds.
Keywords: Argentina; Polanyi; institutions; marketization; post-neoliberalism; soy; uneven development

Local development versus neoliberal globalization project: reflecting on market-oriented cities - Abdalla, Márcio Moutinho; Faria, Alexandre (Desarrollo local frente al proyecto de globalización neoliberal: reflexión sobre las ciudades orientadas al mercado., 2019)
The purpose of this article is to discuss what has being disseminated and reproduced as local development, seeking to understand the problems arising from this phenomenon, particularly highlighting the promotion of market-oriented cities. We question the processes of development and public policies, advancing in the debate based on Karl Polanyi's double-movement thesis duly revisited and updated historically and geographically. As contributions, we highlight the engagement with de-coloniality to treat temporal and geo-epistemic gaps of the Polanyian thesis. In addition, it is possible to identify that the Polanyian counter-movement depends on the actions of several social actors, with emphasis on societies and governments, through public policies. (English)
Keywords: Brazil; cidades orientadas ao mercado; ciudades orientadas al mercado; countermovement; desarrollo local; desenvolvimento local; doble movimiento polanyiano; double movement; duplo movimento polanyiano; globalization; government policy; industrialization; local development; market-oriented cities; neoliberalism; neoliberalismo; políticas públicas; public policy; social conditions in Brazil

Polanyi in Zeiten des Populismus - Bärnthaler, Richard (Wirtschaft und Gesellschaft, 2019)
Keywords: HOLMES, Christopher; POLANYI, Karl, 1886-1964; Polanyi in Times of Populism: Vision & Contradiction in the History of Economic Ideas (Book); book review; nonfiction

Who Plans Our Political Economy? A Solidarity Economy Vision for Democratic Political Economy Planning - Gilbert, Geoff (Harvard Unbound, 2019)
The Democratic Party's current left-wing resurgence shows that significant popular support exists for an expanded vision of fundamental rights for all people: rights to public health care and higher education; affordable housing; living-wage jobs; and a Green New Deal that transitions human society to ecological sustainability while also reducing inequality. But what are the best institutional means to provide this expanded vision of fundamental rights? This paper argues that we must stop expecting or hoping that highly centralized state and corporate institutions, which reserve rights to ownership and control for the few, will produce any results other than those that benefit the few. I argue that in order to provide an expanded vision of fundamental rights we must create a democratic political economy comprised of institutions that are themselves democratic and controlled by the people they are meant to serve. Guided by Karl Polanyi's insight that the fictitious commodification of labor, land, and money has made human society an accessory of the economic system, I propose a vision for creating, starting at the city level, democratic systems for controlling land, labor, and money. The vision--inspired by global movements including the Zapatistas in Mexico, the Movement of Landless Workers in Brazil, the Kurds in Rojava in Northern Syria, and the municipalist movement in Spain--calls for democracy in the workplace through worker cooperatives, local democratic ownership and control of land through land banks, community land trusts, and a land value sales tax, and democratic banking through public banks at the city level. By demonstrating the viability of democratic political economy institutions at the local level, organizers can amass resources to build toward broader systemic transformation.
Keywords: fictitious commodification; fundamental rights; green new deal

De la gran transformación a la gran financiarización. Sobre Karl Polanyi y otros ensayos - Quiroz, Omar (Foro Internacional, 2019)
Keywords: From the Great Transformation to the Great Financialization (Book); book review

Karl Polanyi: Ein Denker für die heutige Zeit - Thomasberger, Claus (Wirtschaft und Gesellschaft, 2019)
Keywords: DALE, Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI, Karl, 1886-1964; book review; nonfiction

Regulating labour dispatch in China: A cat-and-mouse game - Xiaojun, Feng (China Information, 2019)
This article suggests cautious optimism toward the prevailing Polanyian countermovement discourse by providing a timely and comprehensive examination of the enforcement of the labour dispatch regulation in China. Since the enactment of the regulation, some enterprises have narrowed the remuneration gap between agency workers and formal employees, while others have retained a large gap in overtime pay, bonuses, and welfare benefits between these two groups of workers. The regulation has reduced the number of agency workers, but has invoked the abuse of the more precarious 'outsourced' workers as well. The regulation has had little effect on limiting the use of agency labour to temporary, auxiliary, or substitute positions, raising the requirements of engaging in the labour dispatch business, or stabilizing the employment of agency workers. This article contributes to the extant literature on regulatory enforcement by examining the effects of non-standard employment regulation, highlighting the variance of labour law compliance among enterprises with different types of ownership, and demonstrating how China's ongoing transformation from a planned to a market economy since the 1980s and from high growth to a new normal since 2010 has fundamentally constrained the full implementation of its labour protection regulation.
Keywords: China; agency workers; countermovement; employment; labor market; labour dispatch; labour market; labour market regulation; law enforcement; new normal; outsourced workers; precarity

Economy–society tensions in the Eurozone: the "anti-democratic virus" revived - Markantonatou, Maria (Capitalism in Transformation, 2019)
This chapter draws on Polanyi’s analysis of the economy-democracy tension to discuss today’s crisis in Greece and the Eurozone. First, some of the economic and social effects of the Greek austerity programme are discussed with reference to his observations on liberal international interventionism in the interwar period. Secondly, the chapter looks at the ways in which democratic outcomes (elections, referenda, parliamentarian decisions, etc.) in Greece and elsewhere were, during different crisis episodes following 2010, put aside in favour of market discipline and austerity doctrines. It is argued that Polanyi’s thesis on the “mutual incompatibility” between capitalism and democracy (the core of what he termed the “anti-democratic virus”) is crucial for understanding today’s crisis and crisis management in the framework of Eurozone’s liberalism.
Keywords: Eurozone crisis; Greece; fascist virus

Karl Polanyi and the Global Network Inspired by His Work - Mendell, Marguerite; Aulenbacher, Brigitte; Novy, Andreas (Österreichische Zeitschrift für Soziologie, 2019)